An Ostrowski Type Inequality for Twice Differentiable Mappings and Applications - Erden, Samet; Budak, Huseyin; Sarikaya, Mehmet Zeki (Mathematical Modelling and Analysis, 2016)
We establish an Ostrowski type inequality for mappings whose second derivatives are bounded, then some results of this inequality that are related to previous works are given. Finally, some applications of these inequalities in numerical integration and for special means are provided.